An auxiliary design system for industrial heat supply system considering carbon reduction benefit. Issue 1 (1st February 2023) - Ren, Jiayi; Wang, Fei; Fan, Zikai; Han, Siwei; Zheng, Jiaqi
Abstract: Decarbonization of industrial process heating plays a crucial role in China's carbon neutrality strategy. Traditionally, industrial users make decision on heat supply system design based solely on economy, with little regard for carbon emission. This study proposes an auxiliary design system to help the designers choosing proper industrial heating supply scheme considering carbon reduction benefit. Through traversal the existing scheme database, all feasible solutions are screen out and then evaluated by calculating an proposed comprehensive economy evaluation index. The comprehensive economy evaluation index takes carbon reduction as revenue since industry users will be able to trade their carbon emission rights at the carbon markets though CCER programs in the future. Future carbon price given by the carbon price prediction module is used to calculate the revenue user can get from carbon reduction. Grid emission factor prediction module makes prediction for changing grid emission factor, which is also involved in the evaluation to consider the benefit from continuously increasing green power in the future. A case study is given with heating demand data of a food factory to shown that the proposed method can reflect the value of carbon reduction, which helps to promote low-carbon technologies in the future.